2019
DOI: 10.1136/bmjqs-2019-009897
|View full text |Cite
|
Sign up to set email alerts
|

Passing the acid test? Evaluating the impact of national education initiatives to reduce proton pump inhibitor use in Australia

Abstract: BackgroundProton pump inhibitor (PPI) use is widespread. There have been increasing concerns about overuse of high-dose PPIs for durations longer than clinically necessary.ObjectiveTo evaluate the impact of national education initiatives on reducing PPI use in Australia.DesignPopulation-based, controlled interrupted time series analysis of PPI dispensing claims data for Australian adults from July 2012 to June 2018; we used statin dispensing as a control.InterventionsA year-long educational initiative led by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Previous research from Australia has reported mixed impacts of deprescribing initiatives and it is unclear why the growth in PPI use has slowed. 33,34 These prevalence figures are slightly below that reported in the Icelandic population 14 and estimated in the UK population, 1 but nearly double that reported in the Danish population. 2 Similar to these population based studies, we found that more females used and initiated PPIs than males.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous research from Australia has reported mixed impacts of deprescribing initiatives and it is unclear why the growth in PPI use has slowed. 33,34 These prevalence figures are slightly below that reported in the Icelandic population 14 and estimated in the UK population, 1 but nearly double that reported in the Danish population. 2 Similar to these population based studies, we found that more females used and initiated PPIs than males.…”
Section: Discussionmentioning
confidence: 72%
“…We used the Australian Bureau of Statistics' mid-year population estimate for Australia on June of the financial year as the denominator for both measures. 31 We stratified prevalence and incidence estimates by sex and age groups (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50-64, 65-74, 75-84 and 85 years and older). We further stratified prevalence and incidence estimates by PPI medicine strength -standard strength, high strength and low strength (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In this issue of BMJ Quality and Safety, Bruno and colleagues examined the impact of a national educational intervention aimed at reducing outpatient PPI prescriptions in Australia. 19 Australia's NPS MedicineWise (previously the National Prescribing Service) developed the study intervention released in association with Choosing Wisely Australia's similar educational materials and alerts highlighting the importance of reducing or ceasing PPI prescribing in the absence of specific indications. The programme began with mailings to general practitioners (GPs) showing data about their own PPI prescribing compared with other GPs nationwide.…”
mentioning
confidence: 99%
“…60 Although education is helpful, a national Australian study suggested that imposing restrictions on subsidized use of PPIs is even more effective. 49 One concern is the PPI-induced gastrin elevation secondary to hypoacidity and the subsequent hypergastrinemia-related rebound hyperacidity and dyspeptic symptoms following discontinuation of the PPI; the long-term gastrin elevation may have carcinogenic effects, raising concerns about consensus for deprescribing strategies. 61…”
Section: Minimize Misuse: An Opportunity For Deprescribingmentioning
confidence: 99%